Chemical quality ofgroundwaters and fluoride concentrations in the district of Dassa-Zoume, Southern Benin.. - DJOSSOU, MEDESSÈ DAVID; DJOSSOU, ALFRED; BIGOT, KOFFI ANDRÉ (My University, 2017)
Like many African countries. the groundwaters of sorne regions in Benin have fluoride concentrations above the WHO guiùelines (0.7 to 1.5 mg/L). The fluoride is llseful against caries and hardens the enamet At higher concentrations. it weakens the bones or causes crystallization points implying the appearance of arthritis deforming joint: it is fluorosis. Fluorosis is a public health problem due to its complication in bone fluorosis. It becorncs an aesthetic problem and a daily oncern for the patients. People discover spotted, brownish and disharmonious teelh when the patient smiles. We propose to carry out a study on a sample of the populations of the district of Dassa-Zoumè in arder to evaluate lhe tluoride rate contained in groundwaters and the impacts on teeth. A transversal. descriptive and allalytical study was conducted. It covered 1,002 PUPlts trom 4 to 18 years of primary and secondary schools ID Dassa-Zoume. The study was carried out in two phases: wells and weil water extraction trom Dassa-Zoume; a total of 24 boreholes were analyzed. Questionnaires directly about dental examination were administered and filled. The fluoride concentration rangeù between 0.29 and 4.3 mgjL with a mean of L87 mg/L. The statistical analysis carried out for p <0.05 showed no correlation between the Fand the four major elements (Ca +, N03-, NO" and NH4t), but this correlation is positive with the evolution of pH between 6.44 and 7.08 for an average of 6.83. There was an overaU prevalence of 12.2% with 95% CI: flO.2 to 14.3%J. il CAO of 0.23 with 139 decayed teeth, 86 tceth absent and 01 tooth c1osed. The distribution of tluorosis at the sample level showed that 61.4% of the pupils had an evident nuorosis. The results of our survey showed Ùle importance of lreatment towards the Dassa-Zoume populations' needs. Only preventive programs cOlild redllce the number of oral diseases.
Keywords: Fluoride - fluorosis - prevalence - Dassa - Benin.